2014
DOI: 10.1007/s10802-014-9911-8
|View full text |Cite
|
Sign up to set email alerts
|

Interrelations of Maternal Expressed Emotion, Maltreatment, and Separation/Divorce and Links to Family Conflict and Children’s Externalizing Behavior

Abstract: Research has documented that maternal expressed emotion-criticism (EE-Crit) from the Five-Minute Speech Sample (FMSS) predicts family conflict and children’s externalizing behavior in clinical and community samples. However, studies have not examined EE-Crit in maltreating or separated/divorced families, or whether these family risks exacerbate the links between EE-Crit and family conflict and externalizing behavior. The current study examined the associations between maternal EE-Crit, maltreatment, and separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…Instead, NSSI is most likely when highly heritable trait impulsivity-indexed in childhood by hyperactiveimpulsive (not inattentive) symptoms of ADHD (Ahmad & Hinshaw, 2016)-co-occur with emotion dysregulation. As outlined above, emotion dysregulation is shaped and maintained across development by aversive socialization mechanisms including maltreatment, coercion, and family reinforcement of emotional lability (Cicchetti, 2016;Crowell et al, 2017;Narayan, Cicchetti, Rogosch, & Toth, 2015). This model is summarized in Figure 1.…”
Section: An Elaborated Transactional Perspectivementioning
confidence: 99%
“…Instead, NSSI is most likely when highly heritable trait impulsivity-indexed in childhood by hyperactiveimpulsive (not inattentive) symptoms of ADHD (Ahmad & Hinshaw, 2016)-co-occur with emotion dysregulation. As outlined above, emotion dysregulation is shaped and maintained across development by aversive socialization mechanisms including maltreatment, coercion, and family reinforcement of emotional lability (Cicchetti, 2016;Crowell et al, 2017;Narayan, Cicchetti, Rogosch, & Toth, 2015). This model is summarized in Figure 1.…”
Section: An Elaborated Transactional Perspectivementioning
confidence: 99%
“…The presence of additive effects suggests that close relationships with two or all three parental figures help alleviate stepchild stress. For example, King (2006) and White & Gilbreth (2001) found that close relationships to both a stepfather and non-resident father reduces externalizing and internalizing behaviours in children -behaviours linked to the presence of stressors (Narayan et al 2015). Berg (2004), using longitudinal data, found that the effect of stepfather closeness was only slightly stronger than that of non-resident fathers.…”
Section: Additive or Independent Effects?mentioning
confidence: 99%
“…Developmental psychopathology is often grounded in theories of how individual risk factors, such as genetic predispositions or exposure to stress and trauma, promote or protect against the development of mental or behavioral health problems (e.g., Narayan, Cicchetti, Rogosch, & Toth, 2015; Trucco, Villafuerte, Heitzeg, Burmeister, & Zucker, 2016). These approaches have made important contributions to understanding how genetic and environmental factors interact in the development of psychopathology (Belsky & Pluess, 2009).…”
mentioning
confidence: 99%